Актуальнi питання сучасноï лiнгвiстичноï термiнографiï: функцiйно-когнiтивний вимiр - Zahnitko, Anatoliy (Wiener Slawistischer Almanach, 2023)
The goal of the present research paper is to point out to peculiarities of Ukrainian dictionaries of linguistic terminology and to identify the main possibilities of their improvement by following the accepted rules of the normalization of linguistic terms. This aim implies an attempt to solve the following tasks: 1) to identify the normativity/nonnormativity of a given linguistic term and its conformity with the author’s intentions; 2) to find out peculiarities of the so called left- and right-hand parts of a dictionary entry and to understand the role of additional qualifying elements for composed terms; 3) to reveal the influence of the functional-cognitive approach in the creation of linguistic dictionaries, which leads to a modification of the understanding of terminological units. The novelty of the research lies in the discussion of the most important issues of linguistic terminography with emphasis on the functional-cognitive approach in the production of linguistic dictionaries, as well as in the characterization of the internal semantic network of a dictionary. The article examines many specialized dictionaries in order to calculate the ratio of norm and innovation and the preferences for traditional or new definitions of terms in the dictionary articles.